2004
DOI: 10.1097/01.qai.0000138420.38995.86
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Safety of HIV Protease Inhibitors in Adults

Abstract: Antiretroviral drugs are associated with both short-term and long-term adverse events. Like other HIV drugs, protease inhibitors (PIs) may affect metabolic processes influencing body shape and body tissue composition, appearance, bone integrity, and cardiovascular status. However, numerous confounding variables including age, cigarette smoking, body mass index (BMI), duration of HIV infection, degree of immunodeficiency, concomitant antiretroviral agents, extent of previous treatment, and duration of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 137 publications
0
26
0
1
Order By: Relevance
“…As a class, PIs are associated with clinical off-target effects on lipid and glucose metabolism, manifested by elevated levels of cholesterol and triglycerides, type II diabetes, and a potentially increased risk for cardiovascular complications (30,38). In an independent study published in parallel with this report, Hruz et al (12) used both in vitro and in vivo models to assess the effects of GS-8374 on the glucose and lipid metabolism relative to those of selected clinically approved PIs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As a class, PIs are associated with clinical off-target effects on lipid and glucose metabolism, manifested by elevated levels of cholesterol and triglycerides, type II diabetes, and a potentially increased risk for cardiovascular complications (30,38). In an independent study published in parallel with this report, Hruz et al (12) used both in vitro and in vivo models to assess the effects of GS-8374 on the glucose and lipid metabolism relative to those of selected clinically approved PIs.…”
Section: Discussionmentioning
confidence: 80%
“…In general, the long-term clinical benefit of PIs across all patient populations can be limited by various factors, including longterm safety and tolerability (3,27,38), resistance (36), and drug-drug interactions (18). Among these limitations, the development of viral resistance has been shown to be a major cause of therapy failure (1,43).…”
mentioning
confidence: 99%
“…Within the remaining classes, PIs and nucleoside/tide reverse transcriptase inhibitors (NRTIs) have the greatest effects on lipid metabolism. Most PIs, except for atazanavir, are associated with elevations in TC, triglycerides, and LDL-C [13]. Nonnucleoside reverse transcriptase inhibitors (NNRTIs) can produce increases in TC, LDL-C, and triglycerides; however, substantial increases in HDL-C, especially with nevirapine, may be potentially benefi cial although further studies of the functional anti-infl ammatory properties of HDL-C are needed [14].…”
Section: Disorders Of Lipid Metabolismmentioning
confidence: 98%
“…The abdominal fat accumulation in HIV-infected persons is associated with higher VAT. Factors associated with fat accumulation include use of certain PIs, increased age, greater body mass index, and more advanced HIV disease [12,13]. However, in recent years, one large case-cohort study suggested that increased VAT may not be associated with HIV or antiretroviral therapy [40].…”
Section: Fat Accumulationmentioning
confidence: 99%
“…Although other factors were once associated with lipoatrophy [19,20], exposure to specifi c nucleoside reverse transcriptase inhibitors (NRTIs; particularly stavudine) is now recognized as the major factor associated with lipoatrophy [21,22] mediated by NRTI-induced inhibition of mitochondrial DNA polymerase-gamma [23,24]. Risk factors for fat accumulation have been shown in longitudinal cohort studies to include increased age, higher baseline fat content, greater body mass index (BMI), white race, and low CD4 cell count at ART initiation [25].…”
Section: Fat Redistributionmentioning
confidence: 99%